Sams teach yourself Mac OS X Lion app development in 24 hours - Hoffman, Kevin, 1975- (Sams, 2012)
In just 24 sessions of one hour or less, you can master Mac OS X Lion development from the ground up, and start writing tomorrow's most exciting iOS-style Mac apps! Using this book's straightforward, step-by-step approach, you'll get comfortable with Apple's powerful new development tools and techniques, build engaging user interfaces, integrate data and web services, and take advantage of Apple's latest innovations, everything from gestures and multitouch to iCloud and In-App Purchasing. Every lesson builds on what you've already learned, giving you a rock-solid foundation for real-world success! Step-by-step instructions carefully walk you through the most common Mac OS X Lion development tasks. Quizzes at the end of each chapter help you test your knowledge. By the Way notes present interesting information related to the discussion. Did You Know? tips offer advice or show you easier ways to perform tasks. Watch Out! cautions alert you to possible problems and give you advice on how to avoid them. Printed in full color - figures and code appear as they do in Xcode Get started fast with Mac Developer Center, XCode, Objective-C, and Cocoa Programmatically control OS X Lion's powerful new features Work with Cocoa's powerful Model-View-Controller (MVC) pattern Safely manage memory and fix leaks Create robust, engaging, highly interactive user interfaces Organize Cocoa layouts, controls, bindings, tables, and collections Support gestures and multi-touch events Define user defaults and provide Preference Panes Work with documents, versions, and iOS-style Autosave Make the most of notifications, alerts, sheets, and popovers Use images and animation to make apps more powerful - and more fun Use Core Data to cleanly integrate data into your apps Query and submit data to web services Submit apps to the Mac App Store Support In-App Purchases with StoreKit.